ETNOORNITOLOGI ANATIDAE DI KABUPATEN LOMBOK BARAT - Slamet Mardiyanto Rahayu; Syuhriatin, Syuhriatin (Yayasan Nusantara Hasana Berdikari, 2025)
Sigerongan is one of the villages in Lingsari District, West Lombok Regency, West Nusa Tenggara Province which has biodiversity, one of which is Anatidae. Ethnoornithology is the study of the use of fauna by a community group. This research aims to determine the use of Anatidae by the Sasak tribe community in Sigerongan Village, Lingsar District, West Lombok Regency. There are two species of Anatidae that are used by the community as food, namely: Anas platyrhynchos and Cairina moschata.